Impacto do uso da terra e da estratificação ambiental no assentamento rural Florestan Fernandes sobre a qualidade do solo - Marcatti, Bruna Aparecida (2014)
The objective of this research is to describe and identify the environmental impacts from the transformation of land use processes triggered by the creation of the settlement of Agrarian Reform Florestan Fernandes-Guaçuí. In recent years, some studies hav